EXAMINATION OF ELECTROPHYSIOLOGICAL PARAMETERS OF THE ATRIUMS IN PATIENTS WITH LONG-TERM PERSISTENT FORM OF ATRIAL FIBRILLATION AND VALVULAR HEART DISEASE - A. A. Kulikov; L. A. Bokeriya (Klinicist)
The study objective is to examine electrophysiological parameters of atrial myocardium, characteristics of atrioventricular conduction, and potential factors affecting recurrent atrial fibrillation (AF) in patients with persistent and long-term persistent forms of AF prior to the Labirynth IIIB surgery with single-step correction of valvular heart disease.Materials and methods. The study included 100 adults (48 men, 52 women) with persistent and long-term persistent forms of AF and different valvular heart diseases. Mean patient age was 59 years. Mean AF duration was 4 years. All patients were prescribed antiarrhythmic therapy but it proved ineffective. In 15 % of patients, restoration of the sinus rhythm was attempted through electrical cardioversion but long-term control of the sinus rhythm wasn’t achieved. All patients were diagnosed with organic pathology of the mitral valve. Also, in 80 % of patients, relative insufficiency of the tricuspid valve was detected. Chronic heart failure functional class per NYHA was III. Size of the left atrium was 5 cm, mean left ventricular ejection fraction was 61 %. All patients underwent electrical cardioversion. After successful restoration of the sinus rhythm, endocardial electrophysiology study (EES) of the heart was performed. Then, correction of valvular pathologies and the Labyrinth IIIB surgery were performed. Results. Examination of refractoriness of different parts of the atriums has shown that effective refractory period (ERP) of the atrioventricular node was minimal compared to other parts of the atriums. Maximal ERP duration was observed in the upper part of the right atrium. Therefore, in patients with long history of AF, heterogeneity of atrial myocardium ERP duration is observed. In 17 % of patients, atrial vulnerability was detected. The area of atrial vulnerability was always associated with ERP. Its duration in patients with atrial vulnerability was significantly higher.Conclusion. Long-term mitral valve incompetence and persistent AF lead to anatomical and electrophysiological remodeling of the atriums, which manifests through increased volume of the left atrium, as well as increased duration of intra-atrial conduction and heterogeneity  of refractory periods. EES allows to evaluate these functions of the atrioventricular conduction system and atrial electrophysiological parameters: detect aberrations in conduction through atrial myocardium, dispersion of its refractoriness, and the area of atrial vulnerability. These factors can serve as predictors of AF recurrence.